2017
DOI: 10.1002/chem.201702131
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Chain‐Length Dependence of the Optical and Structural Properties of Diketopyrrolopyrrole‐Based Oligomers

Abstract: Here, we report the synthesis, optical properties, and solid-state packing of monodisperse oligomers of diketopyrrolopyrrole (DPP) up to five repeating units. The optical properties of DPP oligomers in solution and the solid state were investigated by a combination of steady-state and transient spectroscopy. Transient absorption spectroscopy and time-correlated single photon counting (TCSPC) measurements show that the fluorescence lifetime decreases with an increase in the oligomer size from monomer to trimer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The decay of the excited-state absorptions and the recovery of the ground-state bleach show nearly identical kinetics, and the absence of new transient signals or the presence of a rise time indicate that no intermediate excited-state species are formed after photoexcitation. The lack of these features and the short excited-state lifetime further suggests a tightly bound electron–hole pair, which rapidly recombines, which is supported by the short conjugation length (approximately three units) that has been reported for a similar structure …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The decay of the excited-state absorptions and the recovery of the ground-state bleach show nearly identical kinetics, and the absence of new transient signals or the presence of a rise time indicate that no intermediate excited-state species are formed after photoexcitation. The lack of these features and the short excited-state lifetime further suggests a tightly bound electron–hole pair, which rapidly recombines, which is supported by the short conjugation length (approximately three units) that has been reported for a similar structure …”
Section: Resultsmentioning
confidence: 64%
“…As previously observed for similar conjugated polymer systems, P­(DPP-T) , P­(DPP-2T) , and P­(DPP-3T) were found to be nonluminescent in THF solution . Therefore, because of this lack of emission, TA spectroscopy in THF was required to determine the excited-state lifetimes and kinetics of the polymers before and after nanoprecipitation.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…1) by performing concentration, temperature and computational studies, and report on the possibility of tuning the type of aggregate formed using concentration and temperature handles. DPP derivatives have been extensively studied by some of the authors 17 and interesting structure-property correlations have been found in terms of dependence of fluorescence lifetimes on the chain-length of these derivatives. Unlike previous works, the steady state absorption and photoluminescence (PL) spectra for the current DPP derivative show pronounced tails suggestive of presence of one or more type of aggregates.…”
Section: Introductionmentioning
confidence: 99%